Implementasi Sistem Informasi Akademik Berbasis Cloud Computing System di Pondok Pesantren Khairul Ummah 2 Pekanbaru - Suwitno; Ari Sandhyavitri; Dian Yayan Sukma; Rangga Byian Tri Putra; Faldy Syukra Aditya; Muhammad Nizham Firdaus; Ruth Tabita Hutagalun; Widya Kamala; Rivandy Cahyandra (LPPM UMRI, 2024)
Pondok Pesantren Khairul Ummah 2 Pekanbaru, as an Islamic educational institution, faces challenges in managing academic data using a manual and conventional system. This system has caused issues such as limited access, data loss risks, and slow administrative processes. This community service aims to resolve these issues by implementing a cloud-based academic system. The method involves initial observation, needs analysis, system development, and the implementation and evaluation of the system at the pesantren. The results show that cloud computing technology improves efficiency in managing student data, lesson schedules, and attendance in a more structured and accessible manner. This technology also allows staff to access data flexibly from any device connected to the internet. Despite challenges in adapting to the technology, proper training is expected to overcome these obstacles. Overall, the implementation of this cloud-based system provides an efficient, cost-effective modern solution for Pondok Pesantren Khairul Ummah 2 in managing academic and administrative data.